2003
DOI: 10.1194/jlr.m200340-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine plasmalogens prevent the oxidation of cholesterol by reducing the oxidizability of cholesterol in phospholipid bilayers

Abstract: The aims of the present study are to establish an appropriate system for assessing the oxidizability of cholesterol (CH) in phospholipid (PL) bilayers, and to explore the effect of ethanolamine plasmalogens on the oxidizability of CH with the system, through comparing with those of choline plasmalogens, phosphatidylethanolamine, and antioxidant ␣ -tocopherol (Toc). Investigation of the effects of oxidants, vesicle lamellar forms, saturation level, and constituent ratio of PLs in vesicles on CH oxidation reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 42 publications
(34 reference statements)
2
47
0
Order By: Relevance
“…Less than 0.2% of the total radioactivity was found in the aqueous layer. This distribution of the radiolabel is in agreement with the literature values for AAPH-oxidized cholesterol [25]. The presence of SM inhibited the formation of all products to the same extent (results not shown).…”
Section: Oxidation Of Labeled Cholesterolsupporting
confidence: 80%
See 2 more Smart Citations
“…Less than 0.2% of the total radioactivity was found in the aqueous layer. This distribution of the radiolabel is in agreement with the literature values for AAPH-oxidized cholesterol [25]. The presence of SM inhibited the formation of all products to the same extent (results not shown).…”
Section: Oxidation Of Labeled Cholesterolsupporting
confidence: 80%
“…The inhibition was much greater when labeled cholesterol was incorporated into pure SM liposomes, although these liposomes were considerably more turbid compared to the PC-containing liposomes. Although previous studies [25] reported some inhibition of cholesterol oxidation by egg PE, both PE and PS modestly stimulated the oxidation in our experimental system. The reason for this discrepancy is not clear, but there are several differences in the experimental conditions between the two studies.…”
Section: Specificity Of Sm Effectmentioning
confidence: 44%
See 1 more Smart Citation
“…5). DHAP-AT is an important enzyme required for synthesis of plasmalogens (Purdue et al, 1997), which are strong antioxidant phospholipids important for scavenging ROS and preventing cell membrane oxidation (Maeba and Ueta, 2003). Our study suggests that a decrease in DHAP-AT activity reduced plasmalogens, which likely increases the vulnerability of late OL-progenitors to oxidative-stress.…”
Section: Discussionmentioning
confidence: 78%
“…18 Plasmalogens may also act as antioxidants, thus protecting cells from oxidative stress. 19 Rüdiger and colleagues 15 reported the highest concentration of plasmalogens in poractant alfa (3.8 mol%), which is 2.5 times greater than beractant and 4 times greater than SF-RI1. On an in-vitro basis, plasmalogens and PUFA-PL contribute substantially to the lowering of surface viscosity.…”
Section: The Biochemistry Of Surfactantsmentioning
confidence: 99%